TANAFURI AL-KALIMÂT, DHU' FIAL-TA' LIF, TA' QÎDUSALIM - Fuqarra Haqqi; Khairia Linermi Siregar (PT. AHLAL PUBLISHER NUSANTARA, 2026)
Fashahah, as one of the fundamental aspects in the study of balaghah, plays an important role in maintaining clarity, accuracy, and beauty in the use of the Arabic language. Amid the development of modern communication, which demands effectiveness and precision of meaning, language use is often found to neglect linguistic rules, resulting in ambiguity and difficulty in comprehension. This condition demonstrates the importance of a deep understanding of the concept of fashahah as a foundation for establishing proper and effective communication. This study aims to examine the concept of fashahah from the perspective of balaghah, with emphasis on the elements that influence the eloquence of an expression, such as tanafur al-kalimat, dhu‘f al-ta’lif, and ta‘qid al-jumal. This research employs a qualitative method in the form of library research, with linguistic and balaghah approaches through the examination of various classical and contemporary literatures. The findings show that fashahah is a major indicator in assessing language quality, as reflected in clarity of meaning, appropriateness of sentence structure, and harmony in word arrangement. An expression is considered fasih when it is free from linguistic defects, easy to understand, and able to convey meaning effectively. Thus, the concept of fashahah functions not only as a linguistic principle but also as a foundation for creating clear, beautiful, and communicative expression. These findings affirm that understanding fashahah has significant relevance in the learning and use of Arabic, both in academic and practical contexts